Doppler hemodynamic liver index and hepatic elastic modulus: Advanced ultrasonographic techniques for non‐invasive prediction of esophageal varices in cirrhosis - Rana, Abhilasha; Malik, Amita; Krishnan, Venkatram; Thakur, Manisha (Journal of clinical ultrasound, 2022)
Purpose Currently esophagoscopy is the gold standard for assessment of esophageal varices in cirrhosis. Predicting the presence of esophageal varices, varices needing treatment (VNT) and variceal grade by advanced ultrasonographic techniques using a combination of Doppler hemodynamic liver index (HDLI) (quantifying portal hypertension) and hepatic elastic modulus (quantifying hepatic fibrosis) would be a cost‐effective and non‐invasive alternative to routine endoscopy. Methods Our cross‐sectional study consisted of cirrhotic patients diagnosed using clinical features and laboratory parameters. Portal venous Doppler and liver sonoelastography were performed in selected subjects for obtaining measurements of HDLI (portal vein diameter/mean velocity) and hepatic elastic modulus respectively. Within 3 days of ultrasound, the subjects underwent upper GI endoscopy for assessment of presence, VNT and grade (F1, F2, F3) of varices. Subjects were divided into two groups (without and with varices) and data analyzed using XLSTAT. Results A total of 60 subjects (26 without and 34 with varices) were evaluated. Mean Doppler HDLI of subjects with varices was significantly higher (0.72 vs. 0.59, p < 0.0001) with progressive increase in values with variceal grade, being highest in grade‐F3 (mean 0.77). Likewise, mean hepatic elastic modulus was also higher in subjects with varices (28.9 vs. 12.6 kPa, p < 0.0001) and showed progressive increase with grade (51.1 kPa for F3). For predicting presence of varices, maximum accuracy of elastic modulus was at cut‐off of 14.5 kPa (sensitivity, specificity 83% and 84.6%) and Doppler HDLI was at 0.66 (66% and 92.3%). Good inter‐rater agreement was present (κ 0.66). Conclusion Combination of Doppler HDLI and hepatic elastic modulus is an excellent non‐invasive method for predicting the presence, VNT, and variceal grade and may obviate need for routine endoscopic screening in cirrhosis. Combination of Doppler hemodynamic liver index (HDLI) and hepatic elastic modulus is an excellent non‐invasive modality for predicting the presence, varices needing treatment and variceal grade and may obviate need for routine endoscopic screening in cirrhosis.